THE AMBIVALENCE OF THE UNITED STATES IN RETURNING THE HOUTHIS AS GLOBAL TERRORISTS - Anshori, Ahmad Bahrul; Arif, Basyir (UI Scholars Hub, 2024)
The re-designation of the Houthi militant group as a terrorist organisation by the United States (US) could reignite conflict tensions in the Middle East region. This US decision shows the inconsistency of Joe Biden's administration, which had revoked the Houthis' terrorist status at the beginning of his administration. This research aims to analyse the motives for the US decision to re-designate the Houthis as a terrorist group. The method used in this research is an exploratory descriptive qualitative method using data collection techniques, namely observation and literature study. The results of this study conclude that the US's changing attitude towards the Houthis' terrorist status is part of the US strategy to put pressure on the Houthis, because the Iran-backed Houthis are a threat to the US in maintaining its existence in the Middle East Region, especially in Yemen. Yemen's position is very strategic for international trade, because it is the entrance gate for navigation to the Red Sea. The US also has ideological interests in Yemen; it wants to spread the Sunni ideology adopted by Saudi Arabia as its alliance against Iran, which spreads the Shia ideology adopted by the Houthis as its allies